In vivo antioxidant and antiulcer activity of Parkia speciosa ethanolic leaf extract against Ethanol-Induced gastric ulcer in rats - Batran, R.A.; Al-Bayaty, F.; Al-Obaidi, M.M.J.; Abdualkader, A.M.; Hadi, H.A.; Ali, H.M.; Abdulla, M.A. (2013)
Background: The current study was carried out to examine the gastroprotective effects of Parkia speciosa against ethanolinduced gastric mucosa injury in rats. Methodology/Principal Findings: Sprague Dawley rats were separated into 7 groups. Groups 1–2 were orally challenged with carboxymethylcellulose (CMC); group 3 received 20 mg/kg omeprazole and groups 4–7 received 50, 100, 200 and 400 mg/kg of ethanolic leaf extract, respectively. After 1 h, CMC or absolute ethanol was given orally to groups 2–7. The rats were sacrificed after 1 h. Then, the injuries to the gastric mucosa were estimated through assessment of the gastric wall mucus, the gross appearance of ulcer areas, histology, immunohistochemistry and enzymatic assays. Group 2 exhibited significant mucosal injuries, with reduced gastric wall mucus and severe damage to the gastric mucosa, whereas reductions in mucosal injury were observed for groups 4–7. Groups 3–7 demonstrated a reversal in the decrease in Periodic acid-Schiff (PAS) staining induced by ethanol. No symptoms of toxicity or death were observed during the acute toxicity tests. Conclusion: Treatment with the extract led to the upregulation of heat-shock protein 70 (HSP70) and the downregulation of the pro-apoptotic protein BAX. Significant increases in the levels of the antioxidant defense enzymes glutathione (GSH) and superoxide dismutase (SOD) in the gastric mucosal homogenate were observed, whereas that of a lipid peroxidation marker(MDA) was significantly decreased. Significance was defined as p,0.05 compared to the ulcer control group (Group 2).